Is all conflict the same? The role of perceived intensity in understanding its effects. (11th January 2021) - Burnard, Mark; Bruk‐Lee, Valentina; Snihur, Alexander; Allen, Josh
Abstract: While interpersonal conflict at work continues to draw attention, researchers have rarely considered the role that conflict intensity plays in amplifying individuals' affective reactions to it. Hence, this study examines conflict intensity as a moderator of the relationship between interpersonal conflict and perceived stress, physical symptoms, and job satisfaction, through negative affect. A total of 306 employees from various industries participated in this cross‐sectional study. Supporting and expanding an emotion‐centered model of conflict, results indicated that the indirect effects of conflict on the study's outcomes were higher when participants perceived the conflict to be of medium and high‐level intensity.